Rogaten, Jekaterina - (:unkn) unknown (My University, 2026)
My main research is in pedagogy, Higher Education (HE) and psychology. Most of my research is centred on evaluating pedagogical approaches and their impact on students’ progression and attainment. I am also researching the impact of psychological and socio-demographic individual differences on learning, performance and well-being of students. In addition, lately, I have expanded my research focus to include research into teachers’ well-being and what can be done to make the education sector a flourishing environment to work in. Furthermore, my developing research interest involves aligning educational and business sectors to ensure graduates are fit for entering employment/career and supporting well-being in education and employment, as well as increasing the role of AI in education and business.